Przedmiot oceny zachowania z perspektywy ocenianych gimnazjalistów - Jaskulska, Sylwia (Wydawnictwo Naukowe UAM w Poznaniu, 2011)
The subject of this article is the ‘conduct marking’ in Junior secondary school. I present the study results, that can be a source of information on school and can contribute to the debate about condition of Polish education. The results are the following: the educational ideal at school is the conformist attitude, students whose conduct is assessed are not motivated to act or work on improving themselves. Schools don’t support student’s development by preparing for autonomous learning, critical attitude, self-assessment, introspection, initiative, involvement and self-development.
The subject of the conduct mark from a perspective of Junior secondary school students
Keywords: ocenianie zachowania; gimnazjaliści; conduct marking; Junior secondary school students